Survival and cause of death in multiple sclerosis: a 60-year longitudinal population study - Lunde, Hanne Marie Bøe (J Neurol Neurosurg Psychiatry, 2017)
OBJECTIVE: Survival and causes of death (COD) in multiple sclerosis (MS) provide ultimate endpoints. We aimed to investigate survival and COD in a 60-year population-based MS cohort compared with the general population. METHODS: All patients with incident multiple sclerosis (MS) (N=1388) with onset during 1953–2012 in Hordaland County, Western Norway, were included. Data were obtained from patient records at Haukeland University Hospital and linked to the Norwegian COD registry. Survival adjusted for sex, age and disease course were estimated by Kaplan-Meier analyses from birth and from disease onset. Mortality and COD in MS relative to the general population were examined by standardised mortality ratio (SMR). RESULTS: Of 1388 patients, 291 had deceased, mainly of MS (56.4%). Median life expectancy was 74.7 years for MS and 81.8 years for the general population (p<0.001); 77.2 years for women with MS and 72.2 years for men with MS (p<0.001). Life expectancy for patients with relapsing remitting MS (RRMS) was 77.8 years and 71.4 years for primary progressive MS (PPMS) (p<0.001). Overall SMR was 2.7 (p>0.0001); 2.9 in women and 2.5 in men (p=0.0009). SMR was 2.4 in RRMS and 3.9 in PPMS (p<0.0001). SMR from disease onset during 1953–1974 was 3.1; 2.6 during 1975–1996 and 0.7 during 1997–2012 (p<0.0083). No difference in cause-specific deaths were found (p=0.0871). CONCLUSION: We found a 7-year shorter life expectancy and almost threefold higher mortality in MS compared with the general population. A rise in survival in MS was observed during the entire observation period.